An Energy Measuring System using MobileNetV2 Model - Mageshwari, G.; M, Mohammed Yaqub; M, Dhanush Kumar; D, Mugundhan S; M, Harish (Journal of Trends in Computer Science and Smart Technology, 2023)
As health is currently a very prominent concern for many people. More options exist for measuring the health care of people. It is possible to measure the quality of health care in various ways. Taking quality food that has less calories boosts the mind and wellbeing as well as helps us to stay healthy. Regular health checks allow you to detect medical issues at the earliest stage and identify illnesses before they become problematic. Having control in the quantity of daily food consumption helps to avoid unnecessary sickness in the body. In this study, one of the measurement techniques used for measuring the total calories of the daily appetite is described. Measuring food calorie is a way to create awareness among the people about the food they have. These techniques can be used for teaching the public to control their diets according to calories measure.